Building the spectacle : breaking the wall : project for a civic sports precinct at Trafalgar Park, Cape Town - Moronell, Catherine (School of Architecture, Planning and Geomatics, 2015)
This design dissertation follows a narrative process of research and design speculation. The report defines the subject of the project and is the first part of the dissertation. The subject can be divided into the two major themes of: historically defensive territory and voyeurism or peoples' desire for publicness. The project is initiated through this pairing of seemingly antithetical themes. The second part and final outcome is a building proposal. Its function has been formed through my engagement with themes. The resultant programme is a civic sports precinct at Trafalgar Park and Baths in Woodstock, Cape Town. I chose this site for it concealed a hidden narrative in the city. The ruin of an 18th century Dutch defence system in the park was a catalyst for the investigation. Creating a civic recreational space in this guarded public territory (both historically and at present) became the object of my project. The narrative of keeping-out emerges as a socio-historical reading of the site. The possibility of seeing-in between sites of activity and how this informs publicness became the first spatial informant for the design project for public space.